Student Assessment of Application Use Safe Exam Browser (SEB) at Universitas Negeri Padang - Sukrisman Sukrisman; Muhammad Zaidanne A An Al Hafizi; Ranggi Pranata; Muhammad Ikhsan (International Journal of Multidisciplinary Research of Higher Education, 2020)
This research aims to analyze student assessments of the use of the Safe Exam Browser (SEB) application for the final semester exam at Padang State University. This research was conducted using quantitative methods with a survey approach. The data source was taken using a questionnaire from seventy-five respondents who took general courses, all data was then analyzed descriptively. There are thirteen points discussed in student assessment. The research results show that the majority of students at Padang State University have experience using the Safe Exam Browser application and it also makes it easier for every student in the exam. Sometimes there are many obstacles in using it, because this is the first time using the Safe Exam Browser application. The results of this research can be used as initial data for subsequent researchers in studying different issues related to this problem as well as various other issues that are relevant to this context.